1982
DOI: 10.1111/j.1151-2916.1982.tb10404.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Superplasticizers and Calcium Aluminate Hydrates

Abstract: Sodium lignosulfonate and naphthalene and melamine sulfonate formaldehyde condensates, dissolved in lime water, are adsorbed on C4AHU and C&i6. When dissolved in dimethylsulfoxide the same admixtures are adsorbed on CsAHIJ but, apparently, not on C3AHa. The adsorption isotherms of the two polycondensates are very similar but different from those of lignosulfonate. This fact can be attributed to the considerable structural difference between the synthetic admixtures and the lignine derivative. The particle zeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

1988
1988
1996
1996

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…Adsorption isotherms in the aqueous medium are shown at the right-hand side of Figure 11. The zeta-potential was found to decrease linearly as the adsorption increased and stabilized to a constant value when the isotherm reached values approaching the maximum adsorption [20]. The left-hand side of Figure 11 shows the zeta-potential measurements corresponding to the amount of adsorbed admixture.…”
Section: Waste Materials Used In Concrete Manufacturiitgmentioning
confidence: 97%
See 3 more Smart Citations
“…Adsorption isotherms in the aqueous medium are shown at the right-hand side of Figure 11. The zeta-potential was found to decrease linearly as the adsorption increased and stabilized to a constant value when the isotherm reached values approaching the maximum adsorption [20]. The left-hand side of Figure 11 shows the zeta-potential measurements corresponding to the amount of adsorbed admixture.…”
Section: Waste Materials Used In Concrete Manufacturiitgmentioning
confidence: 97%
“…The dispersing action of such admixtures is explained in terms of lowering of zeta-potential, that results upon adsorption of the admixture in the cement paste phase [ 11,19,20]. The dispersing action of such admixtures is explained in terms of lowering of zeta-potential, that results upon adsorption of the admixture in the cement paste phase [ 11,19,20].…”
Section: Waste Materials Used In Concrete Manufacturiitgmentioning
confidence: 99%
See 2 more Smart Citations
“…Massazza et al [42,43] investigated effects of the superplasticizer on C,A hydration. He found that both naphthalene sulfonate and lignosulfonate slowed down the rate of ettringite formation.…”
Section: Effects Of Superplasticizer On Early Hydrationmentioning
confidence: 99%